Efeito das Isoflavonas da Soja na expressão gênica e histomorfometria na glândula adrenal de ratas ovariectomizadas - Marinho, Darci Souza [UNIFESP] (2016)
In the last decades the life expectancy has increased due to socio-economic development and the improvement of medical care provided to population. In this sense most women will experience a post-menopausal stage of life exposing themselves to deleterious effects of estrogen deprivation. This led to the development of hormone replacement therapy, which is mainly used for relief of vasomotor and urogenital symptoms, as well as to reduce osteoporosis and cardiovascular disease risk. In consequence of some contraindications of this method, many studies aim the development of alternative therapies hat can benefit women's health. Among them we can highlight the use of phytoestrogens such as isoflavones, a vegetal no-steroidal compound that induces biological responses by modulating the actions of endogenous estrogens by binding to its receptors. In this study we analyzed the histomorphometry and the gene expression of Ki-67, VEGF and caspase 3 in the adrenal gland of ovariectomized rats treated with estrogen or isoflavones. We used 15 Wistar rats ovariectomized treated with isoflavones estrogen for 30 days. Treatment with estrogen showed a largest increase in the layers of the adrenal than isoflavones. These hypertrofic effects agree with the gene expression elevation of Ki67 and VEGF, which did not occur with the caspase 3, indicating that isoflavones have great proliferative effect on the adrenal gland but no protective effect against apoptosis. Taken together, our results indicate positively the therapeutic potential of isoflavones and can contribute to the development of effective therapies to decrease the symptoms of menopause.